(untitled) (Persona y Derecho, 2018)
STC 130/91 is a good example that shows like they conjugate the formalist positivism and the decisionism realist. The legalist interpretation of Law, mechanist formalism and the theory of the subsunción they conceal a jurist, presumably independent and really subject to the legislator and servant of the power (reductio ad hitlerum), that confuses the positivism like methodology, theory and ideology, that it reduces Law to the formal validity and rejects fue correction pretension. She is a "acrítico" and "simplón" jurist. It shares the formalist positivism with the realist decisionism. On the contrary, integral and critical jurist, rehabilitates the practical reason and the public and critical use of the reason and shares theories of the argumentation and of the legal reasoning that reject the legalist interpretation, the formalist positivism and the realist decisionism.